Hypophosphatasia : phenotypic variability and possible Croatian origin of the c.1402G>A mutation of TNSALP gene - Petković Ramadža, Danijela (Array, 2009)
Abstract: Hypophosphatasia is a metabolic bone disease characterized by bone and teeth hypomineralization due to defective function of tissue-nonspecific alkaline phosphatase (TNSALP). The disorder is caused by various mutations in the TNSALP gene localized on short arm of chromosome 1. Infantile hypophosphatasia is a severe form of the disease inherited as an autosomal recessive trait which presents before age of six months and often has fatal outcome. We report a patient with typical clinical course for infantile hypophosphatasia who was homozygous for the c.1402G>A mutation. The same mutation has been previously associated with a more severe perinatal form also in a Croatian family what indicates a possible common ancestral origin and phenotypic variability potential of c.1402G>A mutation of TNSALP gene